Russia and the West : environmental co-operation and conflict - Hønneland, Geir (Routledge research in environmental politics ;, 2003)
Hønneland assesses current environmental discourses and applies this analysis to look at the relations between Russia and the West with regards to environment problems. It includes three in-depth case-studies on environmental problems, living marine resources, nuclear safety and air pollution.